PM.43 Low Dose Aspirin in Pregnancy. (26th April 2013) - Boban, DD; Ferguson, E; Farquharson, M
Abstract : Introduction: Hypertensive disorders in pregnancy are associated with significant risks to both mother and baby. NICE recommends women at high risk of pre-eclampsia to be given 75 mgs of Aspirin from 12 weeks gestation until delivery. Aim: To review current practise on use of low dose aspirin in pregnancy for prevention of pre-eclampsia and to establish safety and benefit of its use. Method: Data were collected retrospectively for 295 patients who booked in for antenatal care between Jan 2010 and Jan 2011. The presence of risk factors for pre-eclampsia, use of low-dose aspirin, antenatal complications and delivery outcomes were recorded on a database and analysed. We investigated whether all eligible women were given aspirin and compared outcomes amongst those eligible who were given aspirin against those eligible who were not given aspirin. Results: 26% of all antenatal bookers were eligible for low dose aspirin of which only 18% were given aspirin. None of the patients who were eligible and prescribed aspirin developed pre-eclampsia as opposed to 7% in those who were eligible and did not receive aspirin. There was also a reduction in induction of labour (21% and 38%) with use of low dose aspirin, but no influence on gestation at delivery, mode of delivery, birth weight or admission to NNU. Conclusions: The use of low-dose aspirin is safe with no side effects in study group and beneficial in prevention of pre-eclampsia. Midwives have been issued with pocket guides to indications for aspirin to improve compliance.